Expression profile of telomere-associated genes in multiple myeloma - De la Guardia, Rafael Díaz (2012)
To further contribute to the understanding of multiple myeloma, we have focused our research interests on the mechanisms by which tumour plasma cells have a higher survival rate than normal plasma cells. In this article, we study the expression profile of genes involved in the regulation and protection of telomere length, telomerase activity and apoptosis in samples from patients with monoclonal gammopathy of undetermined significance, smouldering multiple myeloma, multiple myeloma (MM) and plasma cell leukaemia (PCL), as well as several human myeloma cell lines (HMCLs). Using conventional cytogenetic and fluorescence in situ hybridization studies, we identified a high number of telomeric associations (TAs). Moreover, telomere length measurements by terminal restriction fragment (TRF) assay showed a shorter mean TRF peak value, with a consistent correlation with the number of TAs. Using gene expression arrays and quantitative PCR we identified the hTERT gene together with 16 other genes directly involved in telomere length maintenance: HSPA9, KRAS, RB1, members of the Small nucleolar ribonucleoproteins family, A/B subfamily of ubiquitously expressed heterogeneous nuclear ribonucleoproteins, and 14-3-3 family. The expression levels of these genes were even higher than those in human embryonic stem cells (hESCs) and induced pluripotent stem cells (iPSCs), which have unlimited proliferation capacity. In conclusion, the gene signature suggests that MM tumour cells are able to maintain stable short telomere lengths without exceeding the short critical length, allowing cell divisions to continue. We propose that this could be a mechanism contributing to MM tumour cells expansion in the bone marrow (BM). © 2012 The Authors Journal of Cellular and Molecular Medicine © 2012 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.